Rheological characterization of amaranth protein gels - Avanza, María Victoria (2005)
Gel forming properties of amaranth proteins at different thermal conditions and protein concentration were studied. Gel point (G′ and G″ crossover) and gelation kinetics (G′ vs. time) were analyzed. The type of gel formed from the rheological point of view was studied analyzing the rheograms obtained from frequency sweeps. Texture properties of cold-set gels were analyzed by TPA assays. Minimum conditions for gelation were 7%, w/v and 70°C. Elasticity of heated dispersions and gels increased with the increase of protein concentration. A high value of the network structure index was observed. This behavior could be related to the great proportion of disulfide bonds formed during amaranth protein gelation. At temperatures above 70°C (80, 90 and 95°C), gelation of dispersions (15%, w/v) took place at times less than 5 min. A first order kinetic gelation process with reaction rate specific constant values that increased with the increase of heating temperature was observed. A rapid denaturation of globulins followed by sulfhydryl/disulfide interchange reactions between protein molecules conduced to a gelation phenomenon enhanced by protein aggregation. Gels prepared over critical conditions (T>70°C, protein concentration >7%, w/v) presented a strong gel-like behavior. These type of gels were elastic in nature (tan δ<0.1), of high hardness, fracturability and cohesiveness, although presented low adhesiveness. Depending on protein and thermal conditions, amaranth proteins were able to form self-supporting gels that could be applied in different gel-like foods.